Efeito de programas de aplicação de fungicidas no progresso da ferrugem, no seu controle e na área foliar da soja - Fiallos, Felipe Rafael Garcés (2010)
The soybean rust, caused by Phakopsora pachyrhizi Sydow & Sydow, occurs in most soybean production regions of Brazil. In the State of Rio Grande do Sul the disease intensity is limited by a lower amount of rain along crop cycle. The crop season of 2009-10, however, showed earlier and more intense occurrence of disease, which allowed studies on disease progress, yield loss and control f soybean rust. An experimental field of Nidera 5909 RG soybeans was sown on 5/Dec/2009 and split into 64 plots (2.7 x 5 m) and 16 treatments comprising one triazol fungicide (tebuconazol) and a mixture of triazol + strobylurin (epoxiconazol + pyraclostrobin, which were sprayed onto plants once, twice or three times at different plant growth stages (V9, R4, and R5.3). A check treatment was kept 4 without fungicide and a standard treatment was sprayed four times at every 15 days. Soybean rust was assessed seven times at weekly intervals by counting the number of lesions and uredia.cm-2 which were later converted into percent severity for each third part of the plants (lower, medium, and upper). A Licor leaf area meter was used to estimate plant leaf area index at the end of pod filling (R7). The yield components were measured for each third of the plant at the harvest. The final disease severity was over 50% on non-sprayed plots and the differences among plant parts were caused by the amount of initial disease, since the epidemic rates were similar for all thirds (0.13 to 0.14 to Logistic and 0.1 to 0.11 to Gompertz). The IAF varied from 1.96 on non-treated plots to 4.4 on the standard treatment with four sprays of epoxiconazol + pyraclostrobin. Spray programs with two or three sprays began at the stage V9 resulted in higher IAF and higher grain weight on the upper third. The number of pods or grains per plant and the number of grains per pod did not differ among treatments. Spray applications began at V9 resulted in better rust control. The mix of triazol + strobylurin was more efficacious than the triazol alone. Disease increase was mainly driven by the amount of lesions, since the number of uredia per lesion did not vary significantly among treatments. It was also evaluated the relationship between leaf weight and leaf area in plants sampled at the growth stage R7. The leaves were weighted fresh weight (soon after sampling) and for dried weight (after 48 hours of incubation at 65 oC) and related to the leaf area previously measured. The model equations were significant (p < 0.0001, R2 = 0.74 to 0.97) and the leaf area (y) was estimated as y = 45.53xf + 19.03 from fresh weight (xf) and y = 5 176.17xs 75.3 for dried weight (xs). Variation among experimental blocks and the lack of rain during pod filling influenced negatively crop loss estimates